Desarrollo de un GeoPortal utilizando ArcGIS Online con datos del área de salud en el Ecuador - Arias Sánchez, Ricardo Mauricio (2017)
This document corresponds to the technical project for the development of a geoportal with information of the health area in Ecuador using the collaborative GIS web system ArcGIS Online. In order to do that, it obtains free geographical and alphanumeric information in public institutions of Ecuador, and with the aid of free software, the respective processing is organized and performed for its incorporation in the geoportal. All this allows the implementation of several maps and the development of eight applications using the templates of ArcGIS Online. The present work is organized in four chapters that are summarized below: Chapter one: "CONTEXTUAL FRAMEWORK": contains the scope and expected benefits in the Project. Chapter two: "THEORETICAL FRAMEWORK": contains the concepts of Geographic Information Systems, their evolution, the supported formats and application, in addition an introduction to geoportals, cloud computing and the ArcGIS Online platform. Chapter three: "ANALYSIS AND DESIGN": this is about obtaining, sorting and debugging information, as well as the installation and configuration of software tools that will allow us to develop the project and the design of the maps by typology. Chapter four: "GEOPORTAL IMPLEMENTATION": describes the configuration of the geoportal, graphic customization and the creation of maps that will eventually be used in the construction of the eight web applications proposed in the project with ArcGIS Online.